-4x-3=-35

Simple and best practice solution for -4x-3=-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-3=-35 equation:


Simplifying
-4x + -3 = -35

Reorder the terms:
-3 + -4x = -35

Solving
-3 + -4x = -35

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -4x = -35 + 3

Combine like terms: -3 + 3 = 0
0 + -4x = -35 + 3
-4x = -35 + 3

Combine like terms: -35 + 3 = -32
-4x = -32

Divide each side by '-4'.
x = 8

Simplifying
x = 8

See similar equations:

| x^2+4=3x+-8 | | n^5=16 | | (7x+9)=(9x-3) | | 3(-4+7x)=-12 | | 6x^2-15x+10=6x+1 | | 3/5-(-3/8)= | | 16/(-4) | | 3/5-(-3/8) | | 3/5-(-3/8 | | 4y+17=15 | | 0.4b+6=15 | | J/2=5 | | 4(-3x+4)=4 | | 4.5u=31.5 | | 10/3=k/9= | | 3u=4.2 | | 333-63y+8y=3 | | V=1/3(3.14)(25)(16) | | 3.5y+1=15 | | 2/3x-3=2/7 | | X^3-4x^2-16=0 | | 7(5-6x)=497 | | y^2-12y=-20 | | 8x^2-y^2=16 | | 75=-15p | | -6(7+x)=-102 | | 11v-3v=48 | | 3(-5+6x)=129 | | V=1/3~r2(h) | | -x-8=x+4 | | 3m^2n+12mn^2=0 | | 5.2(3+3x)-1.6=14 |

Equations solver categories